THE INTERNET: BREAKING THE RULE OF TEACHING GRAMMAR - Antonius Suratno (Soegijapranata Catholic University, 2007)
III this paper the writer reports the use of the Internet as part of strategy in teaching grammar of English. In such a case, students managed to both experience the wealth of computer technology through the Internet abundant facilities for learning language and the success in grasping better ideas of the language rules. Through this activity, students functioned as